Genetic background of atrial fibrillation: influence of single-nucleotide polymorphisms - Schmidt, Constanze; Ravens, Ursula (Cardiovascular research, 2020)
Commentary on ‘Identification of atrial fibrillation associated genes and functional non-coding variants’, by van Ouwerkerk et al., Nat Commun, 2019.
Gesehen am 20.10.2020